PROCUREMENT SYSTEM IN DRUG DESIGN PHARMACIES HEALTHY DEVELOPMENT - Kunti Kunti; Yuce Yuliani, SKom, MMSI (Jurnal Sistem Informasi, 1999)
Pharmacy is an important effort inhealth. Pharmacy is a community service facilities in providing medicines and supplies other information. Therefore, the above functions requires good management pharmacies and tidy in order to support the progress of these pharmacies. Such efforts will be realized when data recording is done well by a section of the warehouse, sales, purchasing and others. At the Healthy Community Pharmacy purchasing system is still done manually, especially in the issuance of purchase orders and reports. And frequent delays in ordering products.Basically every company expects the existence of a data processing is true and accurate to resolve the problems in data processing and to support decision-making on the part of the company. Therefore in this paper, the authors tried to computerize the processing of data, especially data processing, letter creation process purchase orders and preparing reports using tools for system development. The tools that are used to design the purchasing system in this paper are: FOD, context diagram, DFD, ERD, and Normalization.Given the design of the system is done, the writer tries to mengkomputerisasi purchases of data processing is a discussion of this research writing.